Protocol Based Blood Management in Major Obstetric Haemorrhage- A Case Series - Kannammadathy Poulose Biji; Ravindran Rashmi; Krishnankutty Rekha; Prabhakaran Vineetha; Bengalath Abida (Journal of Clinical and Diagnostic Research, 2021)
Major obstetric haemorrhage remains the leading cause of maternal mortality globally. Irrespective of the etiology of haemorrhage, rapid and efficient intervention using proactive standardised protocols should gain precedence in the management of major obstetric haemorrhage. As the available resources vary between institutions, protocol specific to each institution is important for timely intervention. This case series reports a few successfully managed cases of obstetric haemorrhage by the implementation of institution based Massive Transfusion Protocol (MTP). Two antenatally diagnosed patients with placenta percreta had elective hysterectomy with bladder repair. The massive haemorrhages in both these cases were managed efficiently with the use of MTP without any sequelae. Another case of atonic Postpartum Haemorrhage (PPH) which did not respond to first line management also was treated successfully with the prompt activation of protocol. A case of uterine rupture with haemorrhagic shock was managed with massive transfusion according to protocol and vasopressors and she survived with no major side effects. A case of traumatic PPH which presented with severe anaemia (Hb 4.6gm/dL) could also be successfully resuscitated by the timely activation of MTP.